Dental caries and associated factors in Ethiopia: systematic review and meta-analysis - Zewdu, Tesfu; Abu, Duresa; Agajie, Mulatu; Sahilu, Tamiru (Environmental health and preventive medicine, 2021)
Background Globally, dental caries may be a major public health issue which may be preventable. Many studies have been conducted on dental caries in Ethiopia which present inconsistent results. Objective This meta-analysis was expected to consolidate the findings conducted in various regions of the country and generate country representative information on the burden and its associated factors of dental caries in Ethiopia. Methods Our systematic review and meta-analysis was carried out to estimate the pooled prevalence of dental caries and its associated factors in the Federal Democratic Republic of Ethiopia. Medical specialty databases like ScienceDirect, HINARI, Embase, PubMed, Google Scholar, and Cochrane Library were consistently and exhaustively searched. To determine the aggregate prevalence, studies delineating the prevalence of dental caries and associated factors were included. Important data were extracted employing a standardized data extraction tool ready in Microsoft Excel and imported to the STATA version-13 statistical software package for analyses. To assess non-uniformity, the Cochrane Q test statistics and I 2 test were performed respectively. A random effects model meta-analysis was accustomed to estimate the pooled burden of dental caries. Results The result of thirteen studies disclosed that the overall prevalence of dental caries in the Federal Democratic Republic of Ethiopia was found to be 40.98 (31.62, 50.34). Within the subgroup analysis, the uppermost prevalence was determined in Tigray region (46.59% (24.64, 68.54)) whereas the bottom prevalence was determined in Addis Ababa (34.20% (8.42, 59.97)). Dental caries prevalence was considerably high among study subjects who consumed sweet food (OR= 2.4 (95% CI (1.91, 3.01))). But the presence of dental plaque (OR = 5.14 (95% CI (0.67, 39.39))) and habit of tooth- cleaning (OR = 0.71 (95% CI (0.17, 2.96))) were not statistically significant with the outcome of interest. Conclusion Our meta-analysis found that the prevalence of dental caries was comparatively high, and sweet food consumption was the most risk issue for dental caries in Ethiopia. The Ethiopian Federal Ministry of Health ought to offer a lot of attention to strengthen the oral health care system and also the implementation of community-level interference programs.